2020
DOI: 10.3390/ma13082004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Damping Properties of Recycled Aggregate Concrete Modified with Air-Entraining Agent and Polypropylene Fiber

Abstract: In this study, recycled aggregate concrete (RAC) modified with polypropylene fiber (PP) and air-entraining agent (AGA) was prepared, and the effects of PP and AGA on the static (compressive strength, Young’s modulus, and splitting tensile strength) and dynamic properties (dynamic modulus of elasticity and damping ratio) of RAC were investigated. The experimental results showed that the addition of an AGA and PP had a favorable effect on the damping ratio of the concrete, however, the addition of the AGA had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 24 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…It has been proved that 100% replacement of coarse aggregate by recycled aggregates could enhance the damping property of the concrete, but improvement of damping capacity is less than 10%, although the replacement of recycled aggregates reaches 100% [ 10 , 12 ]. The addition of air-entraining agents in concrete can also improve the damping ratio due to the increased porosity of concrete, and the pores inside work as cushioning bags to absorb vibration, but high porosity negatively affects the mechanical properties of concrete [ 13 ]. Moreover, different fibers such as synthetic fibers, nanofibers, and natural fibers were studied to add to concrete to improve energy dissipation [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that 100% replacement of coarse aggregate by recycled aggregates could enhance the damping property of the concrete, but improvement of damping capacity is less than 10%, although the replacement of recycled aggregates reaches 100% [ 10 , 12 ]. The addition of air-entraining agents in concrete can also improve the damping ratio due to the increased porosity of concrete, and the pores inside work as cushioning bags to absorb vibration, but high porosity negatively affects the mechanical properties of concrete [ 13 ]. Moreover, different fibers such as synthetic fibers, nanofibers, and natural fibers were studied to add to concrete to improve energy dissipation [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with natural aggregate concrete (NAC), recycled aggregate concrete (RAC) damping performance improvement was attributed to various factors, such as the bond between the new‐to‐old interfacial transition zone (ITZ) and different new concrete strengths. Various researches 8–12 in the past have been carried out to improve the damping performance of RAC, and the commonly adopted method is to use polymer materials to modify concrete. According to the literature, it was found that the damping performance of concrete after modification can be improved, but the strength and stiffness will be reduced.…”
Section: Introductionmentioning
confidence: 99%